Classification with linear discriminant analysis of morphological variables in peach (Prunus persica L. Batsch) ‘Jarillo’ in the Santandereana Mountains, Colombia - Quevedo-García, Enrique; Darghan, Aquiles Enrique; Fischer, Gerhard (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
During 2014, in the province of Pamplona, Colombia, a study on the peach variety Jarillo was carried out in order to classify a series of morphometric variables in this crop, grown at three different altitudes (Pamplona, 2,170 m a.s.l., Chitaga, 1,870 m a.s.l., and Pamplonita, 1,670 m a.s.l). The conditional Latin hypercube sampling approach was used to select samples of the trees. In the leaves, the width was measured with the length of the limbs and the limbus area using the software ImageJ. In the fruits, the longitudinal r on the equatorial diameter and dry weight were measured. The linear discriminant analysis technique was applied, which was complemented with boxes diagram by farm with the values of the discriminant function for the samples of the different groups and ended with the scatter plot of the two best discriminant functions. This classification suggested different agronomic management plans for Pamplonita and Chitagá, especially for the harvest that involved the dry weight of the fruits. There is a common area between Pamplona and Pamplonita, which can be attributed to the fact that both are in the Catatumbo basin. The values of length and width of the limbus and limbus area were highly discriminating characteristics in this study and were susceptible to change because of environmental factors. The study concluded that the farms Chitagá and Pamplonita were clearly discriminated according to the measured variables, reaching discriminant function with 89.3% separation in the variables.